How Can Digital Strategy Help Sme’s for Export Expansion of Pepper - Ilham, Davin Firmansyah; Ayundha Evanthi (Business and Investment Review, 2023)
This research aims to analyze how the use of digital strategies can increase of Indoesian Pepper exports. This resrearch using qualitative study methods and literature review methods as a basic for understanding the use digital strategy to provide pepper export. The results of this research can be used as recommendations for businesses, especially SMEs and for begginer exporter, to engage in pepper exports efficiently and effectively strategy.